2022
DOI: 10.3390/diagnostics12010176
|View full text |Cite
|
Sign up to set email alerts
|

Early Routine Biomarkers of SARS-CoV-2 Morbidity and Mortality: Outcomes from an Emergency Section

Abstract: Background. COVID-19 is a severe acute respiratory disease caused by SARS-CoV-2, a virus belonging to the Coronaviridae family. This disease has spread rapidly around the world and soon became an international public health emergency leading to an unpredicted pressure on the hospital emergency units. Early routine blood biomarkers could be key predicting factors of COVID-19 morbidity and mortality as suggested for C-reactive protein (CRP), IL-6, prothrombin and D-dimer. This study aims to identify other early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Our initial measurement of clinical parameters was consistent with others showing elevated CRP and LDH, common acute-inflammatory biomarkers [49, 68, 69]. These have been shown to have a positive correlation with the development of pulmonary lesions during early COVID-19, and consequently with severe COVID-19 and related respiratory complications [70, 71]. We recently found an association of soluble urokinase Plasminogen Activator Receptor with COVID-19 severity, and length of hospitalization [72].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our initial measurement of clinical parameters was consistent with others showing elevated CRP and LDH, common acute-inflammatory biomarkers [49, 68, 69]. These have been shown to have a positive correlation with the development of pulmonary lesions during early COVID-19, and consequently with severe COVID-19 and related respiratory complications [70, 71]. We recently found an association of soluble urokinase Plasminogen Activator Receptor with COVID-19 severity, and length of hospitalization [72].…”
Section: Discussionsupporting
confidence: 87%
“…to have a positive correlation with the development of pulmonary lesions during early COVID-19, and consequently with severe COVID-19 and related respiratory complications [70,71]. We recently found an association of soluble urokinase Plasminogen Activator Receptor with COVID-19 severity, and length of hospitalization [72].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with other similar studies in the literature [12][13][14][15][16][17][18][19][20][21][22]. Those studies, mainly performed in the USA, showed a significant association between the increase in liver function and disease progression or death in patients with COVID-19 [20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Liver damage is likely multifactorial: it may be due not only to direct viral damage, but also due to a systemic cytokine storm, pro-thrombotic state, drug use and abuse during COVID-19, and hypoxic injury [8]. Finally, several studies have investigated the role of liver enzymes on disease progression and mortality [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], showing a relation between the elevation of liver enzymes, considered as a manifestation of liver damage, and the severity of COVID-19 disease. In addition, the impact that the SARS-CoV-2 pandemic has determined on patients with liver disease has been considerable for both outpatient and inpatient management [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…An early risk stratification might help in differentiating patients at higher risk of severe disease to provide an adequate care. Several anamnestic, clinical, and blood sample findings were previously reported to associate with a negative outcome, including obesity and metabolic syndrome [1], hypertension [2], inflammatory biomarkers [3], procalcitonin and D-dimer [4], impaired coagulation [5], and even the amount of time spent in the intensive care unit [6]. However, to date none of these emerged above the others.…”
mentioning
confidence: 99%